Increasing Village Potential Through Small Medium Micro Business Development and Family Empowerment - Yosa Novia Dewi; Khidayatul Munawwaroh; Ziecky Mardoni; Rona Rossa; Febriyanno Suryana; Sadjiran Sadjiran (UNUSA Press, 2022)
The COVID-19 pandemic decreased Micro, Small, and Medium Enterprises (MSMEs). Therefore, This community service program aims to improve community welfare through the development of MSMEs based on local wisdom in Padang Pariaman Regency, West Sumatra. Nan Sabaris District, Padang Pariaman Regency has several MSMEs producing various products, especially Padang Pariaman speciality cakes. Pauh Kambar village is a culinary destination in Nan Sabaris District. Not all MSMEs in the Pauh Kambar Village were well managed. There was potential products development, but their production and marketing were still limited. The main focus of this MSMEs development program was empowerment through business training and mentoring. This program included business management, financial management, product packaging, and online marketing training. In addition, it also performed family empowerment in the target community. This program focused on the strengthening phase of the community empowerment program. The program evaluations showed that the beneficiaries were very satisfied with the training and business monitoring program. In addition, the program was very effective for beneficiaries in business management abilities, marketing management, business motivation, business turnover, and parenting knowledge. Furthermore, beneficiaries had increased a business turnover of approximately IDR 1.5 million/month and an average income of IDR 750 thousand/month after receiving training and mentoring programs. The MSMEs development program and family empowerment are satisfactory and effective for MSMEs actors in Pauh Kambar Village. The community service team will recommend partners receive financial assistance from other programs and build cooperation with various stakeholders.